Single-agent panobinostat for relapsed/refractory diffuse large B-cell lymphoma: clinical outcome and correlation with genomic data. A phase 2 study of the Fondazione Italiana Linfomi. Issue 12 (2nd December 2018) - Zaja, Francesco; Salvi, Flavia; Rossi, Maura; Sabattini, Elena; Evangelista, Andrea; Ciccone, Giovannino; Angelucci, Emanuele; Gaidano, Gianluca; Zanni, Manuela; Ladetto, Marco; Chiappella, Annalisa; Vitolo, Umberto; et al.
Abstract: We investigated panobinostat 40 mg three times weekly in 35 adult patients with relapsed/refractory (R/R) diffuse large B-cell lymphoma (DLBCL). Overall response rate and complete response were 17.1% and 11.4%, respectively. Median progression-free survival (PFS) and overall survival were 2.4 and 7.6 months, respectively. Calculated 12, 24 and 36 months PFS were 26%, 11% and 11%, respectively. Four patients who achieved a sustained CR, continued receiving panobinostat for an overall period of 44, 48, 50, 62 months. Thrombocytopenia grade 3 (5 patients) and 4 (24 patients) represented the main toxic effect, causing dose reduction or treatment suspension in 19 patients. Genomic analysis was unable to identify any relationship between mutations and response; TP53 mutation appeared not to impact the clinical outcome. Overall, panobinostat has a modest activity in R/R DLBCL patients, however it can induce very long lasting responses in some cases. Thrombocytopenia frequently limits the use of this agent.